2005
DOI: 10.1590/s1516-89132005000200013
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of pectin from apple pomace

Abstract: As apple-processing units are now in expansion in Brazil, industrial by-products

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
1
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(133 citation statements)
references
References 5 publications
4
109
1
13
Order By: Relevance
“…The floating pectin coagulate was filtered through a cheesecloth, rinsed with 95 °GL alcohol, and pressed. The pressed pectin was dried to constant weight at 55 °C and cooled in a desiccator; the yield was calculated on a dry weight basis (initial weight of the sample) (Canteri-Schemin et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The floating pectin coagulate was filtered through a cheesecloth, rinsed with 95 °GL alcohol, and pressed. The pressed pectin was dried to constant weight at 55 °C and cooled in a desiccator; the yield was calculated on a dry weight basis (initial weight of the sample) (Canteri-Schemin et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, Pectin extracted using hot acid is low methoxylated due to demethylation and fragmentation of the polygalacturonic chain. Moreover, LM pectin occurs in a broad pH range, at most up to pH 6 [50][51][52][53].…”
Section: Acid Extraction Of Pectinmentioning
confidence: 99%
“…Citric acid can be used to isolate pectin with better gelling properties. However, some studies suggested the use of citric acid because of its higher yield and better quality than other acids [57,58].…”
Section: Acid Extraction Of Pectinmentioning
confidence: 99%
“…Maria Helene and colleagues extracted pectin from apple pomace aiming at establishing the optimum conditions for acid extractionusing citric acid [6].UruthiraKalapathy and Proctor [7], extracted pectin from soy hull using hydrochloric acid and the highest yield obtained was 28%. LEVIGNE Sébastien; RALET Marie-Christine and THIBAULT Jean-Francois [8], used sugar beet as substrate for pectin extraction.…”
Section: Literature Reviewmentioning
confidence: 99%